Comparison of two full-field identification methods for the wedge splitting test on a refractory. Issue 16 (December 2018) - Vargas, R.; Neggers, J.; Canto, R.B.; Rodrigues, J.A.; Hild, F.
Highlights: Fracture mechanics parameters are assessed for a wedge splitting test. Finite Element Model Updating (FEMU) and Integrated DIC (IDIC) are compared. A virtual experiment is analyzed, then followed by experimental analyses. The R-curve behavior of the studied material is obtained for both approaches. The R-curve is compared with independent estimates of fracture energies. Gray level residuals are a powerful tool to check analyses with experimental data. IDIC led to lower residuals and fracture energies were more consistent than FEMU. Abstract: Two full-field identification methods are applied to the Wedge Splitting Test (WST) to obtain crack tip positions, stress intensity factors (SIFs) and T -stress. The first method is based on Finite Element Model Updating (FEMU), and the second is integrated digital image correlation (IDIC). Both are applied to a simplified virtual experiment and then to a cyclic WST. The gray level residuals are used to assess which results are more trustworthy. Fracture energy analyses are performed to validate the estimated R-curves.